CAN TAX POLICY HEAL DISASTER-HIT ECONOMIES? A COMPARATIVE PERSPECTIVE FROM INDONESIA AND THE PHILIPPINES - Kaca Dian Meila; Putri Gantine Lestari; Zihadi Dikri Muhlisin ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2026)
This study aims to compare the implementation and effectiveness of post-disaster tax incentives in Indonesia and the Philippines, both developing countries with high levels of disaster vulnerability. Effectiveness in this study is assessed based on the ability of tax policies to reduce short-term economic pressure, maintain business continuity, and support post-disaster economic recovery. This study employs a contextual comparative qualitative approach using the PRISMA model and content analysis of academic literature, tax regulations, institutional reports, and official government documents published between 2004 and 2025. The findings show that both countries implement a combination of fiscal, administrative, and trade incentives for disaster-affected areas. Indonesia adopts a more centralized approach through national regulations, while the Philippines applies a more decentralized approach involving local governments. Indonesia's centralized system provides greater regulatory certainty but faces coordination and administrative challenges. In contrast, the Philippines demonstrates greater responsiveness to local conditions, although implementation varies across regions due to unequal local government capacities. This study concludes that tax incentives play a supporting role in economic recovery; however, their effectiveness is highly influenced by institutional capacity and coordination within post-disaster fiscal policies.